2009
DOI: 10.1111/j.1748-1090.2008.00079.x
|View full text |Cite
|
Sign up to set email alerts
|

Early introduction of hand‐reared Gorillas Gorilla gorilla to conspecifics at Barcelona Zoo: general procedures and three case studies

Abstract: The purpose of this paper is to describe the early introduction protocols developed for four (1.3) hand‐reared Gorillas Gorilla gorilla that were introduced to conspecifics at Barcelona Zoo. The introduction process for each was initiated when the infants were <1 year old. The introductions began in 1999 and ended in 2001, and the difficulties faced while carrying out such procedures were novel at that time. The protocols had to be improved following the assay error results. In the first instance, the infant G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…The years between 2002 and 2011 have not only shown a decrease in hand rearing but also the social management of hand‐reared infants has improved. Four of the 19 hand‐reared offspring have successfully been reintroduced to their natal groups at an early age (<1 year) (Vermeer, ; Abelló & Colell, ), and two individuals were bottle fed by keepers while being cared for by their mothers.…”
Section: Development Of the Populationmentioning
confidence: 99%
“…The years between 2002 and 2011 have not only shown a decrease in hand rearing but also the social management of hand‐reared infants has improved. Four of the 19 hand‐reared offspring have successfully been reintroduced to their natal groups at an early age (<1 year) (Vermeer, ; Abelló & Colell, ), and two individuals were bottle fed by keepers while being cared for by their mothers.…”
Section: Development Of the Populationmentioning
confidence: 99%
“…These challenges can be exacerbated by instability resulting from introductions of new members and deaths of existing members in bachelor groups. Numerous studies on the introduction of single individuals or the formation of a new group from two previously separate groups have been conducted on zoo‐housed western lowland gorillas (Abelló & Colell, ; Bowen, ; Sunde & Sievert, ). At the Barcelona Zoo, researchers found that infants under 1 year of age were more flexible and adaptable to new situations, while individuals over a year old were more reluctant to engage with keepers or unfamiliar adult gorillas (Abelló & Colell, ).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies on the introduction of single individuals or the formation of a new group from two previously separate groups have been conducted on zoo‐housed western lowland gorillas (Abelló & Colell, ; Bowen, ; Sunde & Sievert, ). At the Barcelona Zoo, researchers found that infants under 1 year of age were more flexible and adaptable to new situations, while individuals over a year old were more reluctant to engage with keepers or unfamiliar adult gorillas (Abelló & Colell, ). Additionally, the adults were found to be more permissive of younger individuals (Abelló & Colell, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The methods and conditions of hand rearing, and the age at reintroduction into a group of conspecifics could affect the social and specifically the breeding performance of the individuals when they reach adulthood (Abelló & Colell, 2006a, 2009). Our study analyses the breeding results of hand-reared gorillas in the EEP population born between 1980 and 2004.…”
Section: Introductionmentioning
confidence: 99%